Implementation of Corporate Social Responsibility (CSR) PT. Samkyung Jaya Garments in Community Economic Empowerment - Purnomo, Joko; Hermawan, Yudan (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
The Corporate Social Responsibility (CSR) program of PT. SAMKYUNG JAYA GARMENTS plays a role in enhancing the economic empowerment of Vilage Wringin Putih community through skill training and business facility assistance. This study aims to analyze the implementation of the CSR program and its impact on participants using a descriptive qualitative approach. Data was collected through in-depth interviews, direct observation, and documentation of the CSR policies of the company. Data analysis used the interactive model analysis method, consisting of data collection, data display, data condensation, and conclusion drawing. The results show that this program provides significant economic benefits to participants, including increased professionalism in business management and opportunities to create jobs for the surrounding community. However, there are some challenges in program implementation, such as limited canteen operational hours, business competition, and price fluctuations of essential goods. To improve the effectiveness and sustainability of the program, a sustainable entrepreneurship strategy is needed to encourage innovation and adaptation in business management. Thus, the CSR program is not only a form of corporate social responsibility but also an instrument to create sustainable economic independence for the community.